2010
DOI: 10.3748/wjg.v16.i40.5092
|View full text |Cite
|
Sign up to set email alerts
|

HNF-4α determines hepatic differentiation of human mesenchymal stem cells from bone marrow

Abstract: Overexpression of HNF-4α improves the hepatic differentiation of human MSCs from bone marrow and is a simple way of providing better cell sources for clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 37 publications
1
23
0
9
Order By: Relevance
“…Considering the hierarchical role of HNF-4α, it raised the possibility that the changes in HNF-4α expression level might lead to the alteration of HNF-3β expression. This idea is supported by our previous research in which we demonstrated that overexpression of HNF-4α significantly upregulates the transcription of HNF-3β [33]. Moreover, we showed that overexpression of HNF-4α could rescue the expression of 2.1–2.4 Kb HBV transcripts under TGF-β1 treatment (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Considering the hierarchical role of HNF-4α, it raised the possibility that the changes in HNF-4α expression level might lead to the alteration of HNF-3β expression. This idea is supported by our previous research in which we demonstrated that overexpression of HNF-4α significantly upregulates the transcription of HNF-3β [33]. Moreover, we showed that overexpression of HNF-4α could rescue the expression of 2.1–2.4 Kb HBV transcripts under TGF-β1 treatment (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…During the first stage of maturation, from 0 to 8 days, A-fetoprotein (AFP), cytokeratin 18 (CK18), cytokeratin 19 (CK19), and transthyretin (TTR) show increased levels [28, 64, 65]. During the second stage, from 9th to 14th day , albumin (ALB), ornithine transcarbamylase (TAT) as well as mRNA levels for VII clotting factor, asialoglycoprotein receptor 1 (ASGPR1), and CYP1A2 member of cytochrome P450 superfamily production are increased while AFP levels are reduced [6568].…”
Section: Resultsmentioning
confidence: 99%
“…During the second stage, from 9th to 14th day , albumin (ALB), ornithine transcarbamylase (TAT) as well as mRNA levels for VII clotting factor, asialoglycoprotein receptor 1 (ASGPR1), and CYP1A2 member of cytochrome P450 superfamily production are increased while AFP levels are reduced [6568]. The last stage of maturation process, from 15th to 21st day , presents hepatic-like cells with functional properties unique to hepatocytes such as increased detoxifying ability, lipid and glycogen storage capacity, urea production, and bile acid secretion [6568]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition to glucose metabolism, our unpublished data also suggest that miR-338-3p might play a role in hepatic lipogenesis. It was reported that HNF-4α played a vital role in regulating hepatic differentiation [37, 38]. Several studies demonstrated the major effect of HNF-4a in the control of genes involved in glucose and fat metabolism [39].…”
Section: Discussionmentioning
confidence: 99%